Comparative Analysis of Emotive Interjections in The English, Russian and Spanish Languages - (:unkn) unknown (MODERN JOURNAL LANGUAGE TEACHING METHODS, 2018)
The relevance of the study is determined by the problem of translating interjections being little covered, as well as by the low degree of studying their semantic fields. Many ones consider interjections as unimportant elements and may not pay attention to them when translating. However, it is worth remembering that interjections are necessary, they attach vitality and expressiveness to our speech. Incorrect translation of interjections can lead to a partial loss of meaning, as well as to not giving the recipient the communicative effect that the author intended to achieve. Also, because of their alienity, interjections are considered one of the most controversial and complex groups of words. For centuries, linguists have been trying to understand what place they occupy in the language system, and to create different concepts. To date, there are many concepts, and some of them contradict each other. The basic ones can be expressed in the form of two oppositions: a word is not a word and a part of speech is not a part of speech. Our discussions unfold around two tasks: 1) To identify the role of interjections in the language. 2) To compare the revealed emotive interjections with their equivalents, given in the translation of the book by Jane Austen Pride and Prejudice into Russian and Spanish, and to reveal their semantic peculiarities.
Keywords: Emotive Interjections; English; Russian; Spanish; translation; context; comparative analysis